Asymptomatic interval in delayed traumatic intracerebral hemorrhage: report of two cases - Kaplan, M; Ozveren, MF; Topsakal, C; Erol, FS; Akdemir, I (Elsevier Science Bv, 2003)
Delayed traumatic intracranial hemorrhage (DTICH) is seen mostly in trauma to the occipitoparietal region by countercoup mechanism. It is most encountered within the first posttraumatic 10 days, particularly in the first 3. Herein, two cases of delayed traumatic intracerebral hemorrhage were discussed, first one presented with headache and vomiting who had been asymptomatic for 168 days after head trauma and the other presented with dysarthria and hyperkynesias after 92 days of asymptomatic interval, either being longer than that of the previous cases reported in the literature. Despite a long time elapse, DTICH should be considered in the differential diagnosis in the patients with history of head trauma that manifests at later stages with intracranial pressure elevation symptoms such as headache, vomiting. (C) 2002 Elsevier Science B.V. All rights reserved.
Keywords: delayed hematoma; head trauma; intracerebral